SKIN BALMS: A SMALL STEP TOWARDS CLEAN AND GREEN SKIN AND BODY CARE - Ms. Akruti V. Awinashe, (IJRDO-Journal of Applied Science, 2025)
Moisturizers are available in different forms ranging from creams, lotions, gels, ointments to balms. They help strengthen the skin and serve as a protective barrier to shield the skin against dryness, itchiness, and irritation as they contain wax. The present study provides an overview of the process of formulating and analyzing skin balms. The main objective was to create, study and analyses various properties of skin balm formulation and their impact on the skin. This was an experimental study on the formulation of five different skin balms using jojoba oil, olive oil, beeswax and emulsifying wax and analyzing the changes that occurred by manipulating the quantities of the ingredients added. Changes in the skin elasticity, moisture content of the skin and overall skin appearance were tested with the use of different laboratory equipment such as cutometer, moisture meter and visiometer respectively. pH and viscosities of various formulations were also noted. Their effects on the skin were recorded after ten minutes and one hour.